Comparison of Co-trimoxazole and Cephalexin Efficacy in Preventing Urinary Tract Infection among Children - Jabar Parhiz; Sara Rahafard; Samaneh Sharifi; Farshid Kompani (Golestan University Of Medical Sciences, 2021)
Background and objectives: Diagnosis and treatment of urinary tract infection (UTI) in children before kidney damage is necessary. The purpose of this study was to compare efficacy of co-trimoxazole and cephalexin in the prevention of recurrent UTI in children. Methods: The study was performed on 100 children aged three months to 14 years who were referred to the Taleghani Pediatric Hospital in Gorgan (Iran) during 2016. The subjects had a history of UTI and required antibiotic prophylaxis to prevent UTI. They were divided into two groups of co-trimoxazole and cephalexin. Data were analyzed using SPSS (version 18) and at significance level of 0.05. Results: Recurrent UTI was observed in eight children (16.0%) taking cephalexin and in six children (12.0%) receiving co-trimoxazole (p=0.56). Urine culture examination revealed Escherichia coli as the causative agent of UTI in six cases (75 %) receiving cephalexin and in five cases (83.3%) receiving co-trimoxazole (p=0.70). It should be noted that unilateral moderate hydronephrosis was the most frequent anomaly (n=26) in the study groups. Conclusion: According to the results of the present study, both cephalexin and co-trimoxazole have similar efficacy in the prevention of UTI among children.